A study on customer perceptions towards the handling of fresh meat and seafood at Hankyu Jaya Supermarket / Siti Dasimah Abdul Latiff - Abdul Latiff, Siti Dasimah
Perception is the process by which consumer attach meaning to incoming stimuli by forming mental, pictures of persons, places and objects. Quality is communicated by choosing those physical signs and cues that people normally used to quality. Freshness of fresh meat and seafood, sold in supermarket play an important role in consumer behaviour such as choice of store is influenced by their perceptions of those stores. The effective method of handing fresh meat and seafood to maintain freshness of the product.